When Beer Is Safer than Water: Beer Availability and Mortality from Waterborne Illnesses - Francisca M. Antman; James Flynn (Institute of Labor Economics (IZA), 2024)
We investigate the impact of beer on mortality during the Industrial Revolution in 18th century England. Due to the brewing process, beer represented an improvement over available water sources during this period prior to the widespread understanding of the link between water quality and human health. Using a wide range of identification strategies to derive measures of beer scarcity driven by tax increases, weather events, and soil quality, we show that beer scarcity was associated with higher mortality, especially in the summer months when mortality was more likely to be driven by waterborne illnesses related to contaminated drinking water. We also leverage variation in inherent water quality across parishes using two proxies for water quality to show that beer scarcity resulted in greater deaths in areas with worse water quality. Together, the evidence indicates that beer had a major impact on human health during this important period in economic development.
Keywords: N33; I15; Q25; 330; mortality; water quality; beer; industrial revolution